2021
DOI: 10.1186/s12940-020-00683-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures of the long-term exposure to air pollution and temperature

Abstract: Background Long-term exposures to air pollution has been reported to be associated with inflammation and oxidative stress. However, the underlying metabolic mechanisms remain poorly understood. Objectives We aimed to determine the changes in the blood metabolome and thus the metabolic pathways associated with long-term exposure to outdoor air pollution and ambient temperature. Methods We quantified met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 62 publications
2
64
1
Order By: Relevance
“…Using metabolomics, several studies have observed alterations in pro-inflammatory and oxidative stress pathways when people are exposed to PM 2.5 . 7,9,10,[12][13][14]17,18 While they have yielded important findings, these studies are limited by the use of a singular time window for exposure to PM 2. 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Using metabolomics, several studies have observed alterations in pro-inflammatory and oxidative stress pathways when people are exposed to PM 2.5 . 7,9,10,[12][13][14]17,18 While they have yielded important findings, these studies are limited by the use of a singular time window for exposure to PM 2. 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of this tool include monitoring the health of bees [49], humans [50], and plants [51]. Additionally, the impact of several pollutants (the focus of our study), such air pollutants [52], metal pollutants [53], and solar filters [54], have also been investigated using metabolite profiling. Our study p resents a novel approach to environmental assessments and a stepping stone in the application of environmental metabolic profiling for monitoring the ecological status of plants affected by oil contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Continued advancement in HRMS instrumentation and computational approaches for data extraction has resulted in their widespread adoption for exposome research [14][15][16]. New applications show the strengths of HRMS to understand chemical phenotypes of exposure for environmental stressors, exposures during pregnancy and other life stages, occupational exposures, and environment-disease relationships [17][18][19][20][21][22][23][24][25]. When combined with additional 'omic measures, HRMS provides a systems biology approach to link exposure to internal dose, biological response, and disease [6].…”
Section: Measuring the Internal Exposomementioning
confidence: 99%